The complete ASP.NET Core 3 API tutorial : hands-on building, testing, and deploying - Jackson, Les (Apress, 2020)
Use this ASP.NET Core API tutorial and straightforward step-by-step guide to build, test, and deploy an ASP.NET Core API to Azure. It will help you code confidently and efficiently, and provides just what you need for context. The book starts with detailing how to set up your development environment, and then introduces a variety of tools and technologies to build, test, and deploy your API. It covers tools such as .NET Core SDK, (Version 3.1), Visual Studio Code, Git, xUnit, Docker, PostgreSQL, Postman, Azure DevOps, Azure, AutoMapper, and many more. Practical guidance is provided so you can achieve a tangible and valuable outcome, and you also are given a dose of theory on REST (Representational State Transfer), JSON, (JavaScript Object Notation), DTOs (Data Transfer Objects), and the MVC (Model View Controller) architectural pattern. What You Will Learn Build an ASP.NET Core API using C#, test it, and deploy it to Azure Understand concepts on Entity Framework Core Gain hard-earned secrets, shortcuts, and gotchas throughout the "build along" Get comfortable with ASP NET Core Environments Be introduced to unit testing, CI/CD pipelines, bearer authentication, and JSON Web Tokens (JWT) Who This Book Is For Developers using the Microsoft stack. Some basic understanding of .NET Core is assumed